The River and the Wall - Masters, Ben, 1988- (Book collections on Project MUSE., 2019)
"When a team of five explorers embarked on a 1,200-mile journey down the Rio Grande, the river that marks the southern boundary of Texas and the US-Mexico border, their goal was to experience and capture on film the rugged landscapes of this vast frontier before the controversial construction of a border wall changed this part of the river forever. The crew--Texas filmmaker Ben Masters, Brazilian immigrant Filipe DeAndrade, Texas conservationist Jay Kleberg, wildlife biologist Heather Mackey, and Guatemalan-American river guide Austin Alvarado--began the trip in El Paso, pedaling mountain bikes through the city's dry river bed. Their path took them on horseback through the Big Bend, down the Wild and Scenic stretch of the river in canoes, and back to bikes from Laredo to Brownsville. They paddled the last ten miles through a forest of river cane to the Gulf of Mexico. As they made their way to the Gulf, they met and talked with the people who know and live on the river--border patrol, wildlife biologists, ranchers, politicians, farmers, social workers, locals, and travelers. They climbed the wall (in twenty seconds). They encountered rare black bears, bighorn sheep, and birds of all kinds. And they sought to understand the complexities of immigration, the efficacy of a wall, and the impact of its construction on water access, wildlife, and the culture of the borderlands. The River and the Wall is both a wild adventure on a spectacular river and a sobering commentary on the realities of walling it off."--